Reflective Integration of Multicultural and Transformative Approaches in Counseling Practice - Prio Utomo; Zubaidah Zubaidah (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2025)
This study aims to explore the integration of multicultural and transformative counseling approaches in counseling practice and their impact on counselee. Using a qualitative reflective-critical approach, the study collected data through in-depth interviews and focus group discussions with counseling practitioners and counselee who have undergone counseling based on both approaches. The results show that, despite challenges in combining techniques from both approaches, counselee reported positive changes in their self-awareness and sense of identity. Practitioners who are sensitive to cultural diversity and adapt their counseling techniques reflectively to meet the needs of counselee are more successful in creating a safe and effective counseling space. This study concludes that the integration of multicultural and transformative counseling can have a significant impact on counselee but requires flexibility and critical reflection from practitioners. The implications of this study highlight the need for ongoing training for practitioners to develop skills in effectively integrating both approaches while considering cultural factors in every counseling session.